Thermal Behaviour, Energy Efficiency in Buildings and Sustainable Construction - Santos, Paulo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue includes 20 contributions from across the world with very interesting and current research topics, such as insulation solutions and CO2 emissions; thermal transmittance of LSF walls; statistics for China's building energy consumption; natural ventilation; thermal behavior of an earthbag building; thermal performance and comfort in a vernacular building; overheating risk under future extreme weather conditions; analytical methods to estimate the thermal transmittance of LSF walls; model simplification on energy and comfort simulation analysis; Trombe wall thermal behavior and energy efficiency of an LSF compartment; new metering hot box for in situ hygrothermal measurement; mechanical and thermal performance of compressed earth blocks; life-cycle assessment of a new house; energy analyses of Serbian buildings with horizontal overhangs; thermal properties of mortar blocks by using recycled glass; prediction of cooling energy consumption building using machine learning techniques; occupants' behavior, climate change, heating, and cooling energy needs of buildings; a new method for establishing a hygrothermally controlled test room; nonintrusive measurements to incorporate the air renovations in dynamic models; and retrofit of existing buildings with aerogel panels.